1989
DOI: 10.2307/1937539
|View full text |Cite
|
Sign up to set email alerts
|

Acorn Harvesting by Florida Scrub Jays

Abstract: We documented number of acorns eaten, cached, and retrieved by Florida Scrub Jays (Aphelocoma coerulescens coerulescens), through one full annual cycle and part of another, in an oak scrub habitat characterized by abundant and reliable annual acorn crops. Jays consumed acorns during all months, with highest consumption from September through February and lowest in June and July. From August through December, most acorns consumed by jays were picked directly from shrubs; during the remaining 7 mo, acorns were r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
67
1

Year Published

1999
1999
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 113 publications
(72 citation statements)
references
References 20 publications
(19 reference statements)
4
67
1
Order By: Relevance
“…Cache revisiting is a hypothesized mechanism by which scatterhoarding animals enhance their memory to remember locations over long periods (DeGange et al 1989;Brodin 1992;Grubb & Pravosudov 1994;Roth et al 2012). We found that Central American agoutis in Panama regularly inspected their caches, which supports a key assumption of the memory enhancement hypothesis.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…Cache revisiting is a hypothesized mechanism by which scatterhoarding animals enhance their memory to remember locations over long periods (DeGange et al 1989;Brodin 1992;Grubb & Pravosudov 1994;Roth et al 2012). We found that Central American agoutis in Panama regularly inspected their caches, which supports a key assumption of the memory enhancement hypothesis.…”
Section: Discussionsupporting
confidence: 70%
“…Eavesdropping thieves may represent a real cost of cache surveillance in this system. The cache revisiting and inspection behaviours observed in this study are fully consistent with the predictions of the memory enhancement hypothesis (DeGange et al 1989;Brodin 1992;Grubb & Pravosudov 1994;Roth et al 2010), yet they do not conclusively demonstrate that cache surveillance actually serves to strengthen spatial memory. Experimental confirmation is needed to determine whether agouti cache surveillance increases long-term spatial memory and is a mechanism facilitating the ability of agoutis to remember cache locations 120 days after burial.…”
Section: Discussioncontrasting
confidence: 39%
“…Long-term cachers store food as a response to a certain lack of food in the future. Species in this class typically engage in intense periods of caching, usually in the late summer or fall [31,66,154,164] and are followed by intervals of limited resources (e.g. winter) during which caches are retrieved.…”
Section: Duration Of Food Storagementioning
confidence: 99%
“…As mentioned above, Peromyscus mice would be the main nocturnal consumer of acorns and, therefore, Aphelocoma birds would be the main diurnal consumer of exposed acorns. Birds are important acorn consumers in oak forest of North America (DeGange et al, 1989), but this group of foragers would be the second main guild of acorn removers, after rodents, in European oak forest (Perea et al, 2012). In our case, Aphelocoma birds seems to be important acorn removers in different habitat types of the fragmented forest under study, which is probably linked to their ability to move across the landscape.…”
Section: Botanical Sciencesmentioning
confidence: 99%
“…In our case, Aphelocoma birds seems to be important acorn removers in different habitat types of the fragmented forest under study, which is probably linked to their ability to move across the landscape. Indeed, because these birds were suggested to be effective long-distance seed dispersers (DeGange et al, 1989), they are likely to move acorns from forest patches towards human-impacted habitats. Nevertheless, the importance of mice and birds as acorns disperser across the different habitat types of this fragmented landscape would require more detailed studies.…”
Section: Botanical Sciencesmentioning
confidence: 99%